Pengaruh Literasi Keuangan, Penggunaan Financial Technology Dan Pengelolaan Keuangan Pribadi Terhadap Gaya Hidup - Ummu Salamah; Ati Sadiah; Iis Aisyah (CV. KAMPUS AKADEMIK PUBLISING, 2023)
This research is motivated by problems that occur in students majoring in Economics Education class of 2020 and 2021, Faculty of Teacher Training and Education, Siliwangi University, Tasikmalaya, namely regarding the lifestyle they live, especially in a frugal or excessive lifestyle in economic matters. The method used is a quantitative approach with a survey method, and explanatory research design, as well as data collection techniques using a questionnaire technique (questionnaire). The population in this study were 218 students majoring in Economics Education class 2020 and 2021, then after carrying out the sampling technique there were 141 people. Sampling in this study used proportional random sampling technique. The results of this study indicate that financial literacy has a significant influence on the lifestyle, then the use of financial technology has a significant influence on the lifestyle, as well as personal financial management. significant influence on the lifestyle. Then overall financial literacy, the use of financial technology and personal financial management have a significant influence on the lifestyle of economic education students class 2020 and 2021. In this study the results obtained R Square 0.579 which means that the three independent variables have an influence of 57.9% on the dependent variable.